Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1161/01.cir.0000135469.82545.d0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Clinical Implications of Aortic Valve Calcification Measured by Electron-Beam Computed Tomography

Abstract: Background-Electron-beam computed tomography (EBCT) is used to measure coronary calcification but not for aortic valve calcification (AVC). Its accuracy, association with aortic stenosis (AS) severity, and diagnostic and prognostic value with respect to AVC are unknown. Methods and Results-In 30 explanted aortic valves, the AVC score by EBCT (1125Ϯ1294 Agatston units [AU]) showed a strong linear correlation (rϭ0.96, PϽ0.0001) with valvular calcium weight (653Ϯ748 mg) by pathology that allowed estimation of cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
163
1
6

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 337 publications
(178 citation statements)
references
References 45 publications
8
163
1
6
Order By: Relevance
“…AVC measurement by MDCT is a fast, simple, noninvasive, highly feasible, widely available, and highly reproducible technique. 15,16 In these studies, intraobserver and interobserver variabilities were <7%. Moreover, for visualization of calcification, CT does not require contrast and can be performed in patients with arrhythmias.…”
Section: Avc-as Diagnosismentioning
confidence: 72%
See 3 more Smart Citations
“…AVC measurement by MDCT is a fast, simple, noninvasive, highly feasible, widely available, and highly reproducible technique. 15,16 In these studies, intraobserver and interobserver variabilities were <7%. Moreover, for visualization of calcification, CT does not require contrast and can be performed in patients with arrhythmias.…”
Section: Avc-as Diagnosismentioning
confidence: 72%
“…13,[23][24][25] In the present large, prospective, cross-sectional study with simultaneous CT scans and Doppler echocardiograms, we observed excellent correlations between hemodynamic severity of AS and severity of AVC load determined by MDCT. 15,23,26,27 However, although the general mechanism of more calcification associated with more severe AS holds true, this large series of patients provides the power to detect for the first time that the relation between AS severity and AVC load in men and women is significantly different (Figure 1). As expected, in patients with mild AVC and less severe AS, the difference between sexes is smaller (Figure 2), and obviously, at that relatively benign end of the spectrum, AVC load, peak aortic velocity, mean gradient, and indexed aortic valve area should be equal in men and women with normal or minimally affected aortic valves.…”
Section: Avc-as Mechanismmentioning
confidence: 91%
See 2 more Smart Citations
“…16 On the basis of these data, MDCT can be considered the preferred imaging technique for both diagnosis and prognosis in patients with poor acoustic windows or left ventricular (LV) dysfunction. 17 …”
Section: Aortic Stenosismentioning
confidence: 99%